Teaching for Creative Competence in General Education Program 2018 - Dung, Mai Thi Thuy (VNU Journal of Science: Education Research; Vol 36 No 2, 2020)
Creativity is not a subject but it is a mission which requires a systematic strategy involving curricurum, teaching pedagogy and assessment (NACCCE, 1999). The Vietnam curricum 2018 has chosen creativity as one of three general competences that students need improving (MOET, 2018a). This is indeed an innovation in education because it shifts from knowledge-based teaching to competency-based approach. The main aim of this papaer is to investigate the tendency and theory of creativity in developed countries then examine teaching pedagogy for creative competence with a belief that it is one of the best practice of implementing the curriculum 2018.